Almost American Girl : An Illustrated Memoir - Ha, Robin; Carmichael, Alison (New York, NY : Balzer + Bray/Harper Alley, imprints of HarperCollinsPublishers, 2020)
"For as long as she can remember, it's been Robin and her mom against the world. Growing up as the only child of a single mother in Seoul, Korea, wasn't always easy, but it has bonded them fiercely together. So when a vacation to visit friends in Huntsville, Alabama, unexpectedly becomes a permanent relocation--following her mother's announcement that she's getting married--Robin is devastated. Overnight, her life changes. She is dropped into a new school where she doesn't understand the language and struggles to keep up. She is completely cut off from her friends in Seoul and has no access to her beloved comics. At home, she doesn't fit in with her new stepfamily, and worst of all, she is furious with the one person she is closest to--her mother. Then one day Robin's mother enrolls her in a local comic drawing class, which opens the window to a future Robin could never have imagined"--Provided by publisher.
Keywords: Ha, Robin -- Comic books, strips, etc; Cartoonists -- Biography -- United States; Women cartoonists -- Biography -- United States; Women illustrators -- Biography; Women immigrants -- Biography; Emigration and immigration -- Comic books, strips, etc; Immigrants -- Comic books, strips, etc; Mothers and daughters -- Comic books, strips, etc; Single mothers -- Comic books, strips, etc; Teenage girls -- Comic books, strips, etc; Koreans -- Comic books, strips, etc -- United States; Stepfamilies -- Comic books, strips, etc; Korean American families -- Comic books, strips, etc; Korean Americans -- Comic books, strips, etc; Comic books, strips, etc -- Comic books, strips, etc -- Authorship; Graphic novels -- Comic books, strips, etc -- Authorship; Graphic novels; Comics (Graphic works); Autobiographies; Autobiographical comics; Nonfiction comics